CULTURALLY-RESPONSIVE MATHEMATICS EDUCATION: DEVELOPMENT AND VALIDATION OF AN ETHNOMATHEMATICS-BASED ILLUSTRATED STORYBOOK FOR TEACHING THREE-DIMENSIONAL GEOMETRY TO SIXTH-GRADE STUDENTS - Raina Melati; Andi Asrafiani Arafah; Makmun Makmun; Sukriadi Sukriadi (Lembaga Penelitian Mahasiswa Penalaran UNM, 2025)
This study aims to develop innovative ethnomathematics-based learning media in the form of picture storybooks, applied to 26 sixth-grade students of SD Islam Al Azhar 47 Samarinda. The type of research used is research and development, utilizing the ADDIE model, which is divided into five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques are carried out through questionnaires, interviews, and observations. Media testing is conducted through validation by material experts, language experts, and media experts. The evaluation during the trial proceeded relatively smoothly. This research is currently limited in scope, so it is necessary to develop broader variables to obtain a more comprehensive picture.